Nilai Sikap dan Keputusan Kerja dalam Perspektif al-Qurán - Tarihoran, Wahdan Sanur (Program Studi S3 Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
This research is an attempt to describe and align the study of organizational behavior in the Western worldview with the text rules found in the Qur'an as the main reference of Muslims. This study takes studies from several books and research that have been published as primary and secondary data. From the results of the study found the Qurán taught his people the importance of values, attitudes, and work decisions. The spiritual values of Islam listed in the Qur'an are the main values that Muslims must uphold so as to reflect appropriate attitudes and produce decisions that are in line with the rules, conditions and do not contradict the values contained in the Qur'an. This research shows that working in the view of Islam is part of Worship, so all decisions taken must be oriented towards the good of the world and the hereafter and reflected in the attitude of work that is a manifestation of the values ingrained in each Muslim individual.